The Edinburgh companion to contemporary Scottish literature - Schoene-Harwood, Berthold (Online access with purchase: JSTOR., 2007)
The Edinburgh Companion to Contemporary Scottish Literature examines the ways in which the cultural and political role of Scottish writing has changed since the country's successful referendum on national self-rule in 1997. In doing so, it makes a convincing case for a distinctive post-devolution Scottish criticism. Introducing over forty original essays under four main headings - 'Contexts', 'Genres', 'Authors' and 'Topics' - the volume covers the entire spectrum of current interests and topical concerns in the field of Scottish studies and heralds a new era in Scottish writing, literary criticism and cultural theory. It records and critically outlines prominent literary trends and developments, the specific political circumstances and aesthetic agendas that propel them, as well as literature's capacity for envisioning new and alternative futures. Issues under discussion include class, sexuality and gender, nationhood and globalisation, the New Europe and cosmopolitan citizenship, postcoloniality, as well as questions of multiculturalism, ethnicity and race. Written by critics from around the world - and by several creative writers - the work of solidly established Scottish authors is discussed alongside that of relative newcomers who have entered the scene over the past ten years or currently emergent writers who are still in the process of getting noticed as part of a new literary avant-garde. Key Features Defines a new period in Scottish literary history: 'post-devolution Scottish literature' Introduces over forty original essays under four main headings - 'Contexts', 'Genres', 'Authors' and 'Topics' Positions literature within the broadest possible cultural framework, from history, politics and economics to new creative technologies, ecology and the media Likely to become the 'standard' work of criticism appealing to students, teachers, researchers and critics as well as to a general readership interested in Scottish literary affairs